Проблеми розвитку інтелектуальної власності в Україні - Яковенко, Р. В.; Yakovenko, R.; Дудченко, О. В.; Dudchenko, O. (София : „Бял ГРАД-БГ” ООД, 2015)
У тезах визначено негативні тенденція до зниження інноваційної активності українських підприємств In the theses, a negative tendency has been identified for reducing the innovation activity of Ukrainian enterprises
Problems of Intellectual Property Development in Ukraine
Keywords: економічне зростання; інтелектуальний капітал; інтелектуальна власність; інноваційна модель; economic growth; intellectual capital; intellectual property; innovative model